BIMBINGAN ADAB SANTRI PONDOK PESANTREN DARUSSALAM BLOKAGUNG KARANGDORO TEGALSARI BANYUWANGI MELALUI KAJIAN KITAB ADAB AL ‘ALIM WAL MUTA’ALLIM - Afif Mahmudi (Institut Agama Islam Darussalam Blokagung Banyuwangi, 2021)
This thesis discusses the Guidance of Adab Santri Putra Pondok Pesantren Darussalam Blokagung Karangdoro Tegalsari Banyuwangi Through the Study of Adab Al 'Alim wal Muta'allim Book. This study aims to determine: 1) The implementation of the guidance of the male students of Class 3 Ula through the study of the Adab Al 'Alim wal Muta'allim book at the Darussalam Islamic Boarding School Blokagung Karangdoro Tegalsari Banyuwangi. 2) Application of adab material in the Adab Al 'Alim wal Muta'allim Book for male students of Class 3 Ula at the Darussalam Islamic Boarding School Blokagung Karangdoro Tegalsari Banyuwangi. This study is intended to answer the following problems: (1) How is the Implementation of Guidance for Male Santri Class 3 Ula through the study of the Adab Al 'Alim wal Muta'allim book at the Darussalam Islamic Boarding School Blokagung Karangdoro Tegalsari Banyuwangi? (2) How is the application of the material about Adab in the Adab Book of Al 'Alim wal Muta'allim for male students of Class 3 Ula at the Darussalam Islamic Boarding School Blokagung Karangdoro Tegalsari Banyuwangi? These problems were discussed through a field study at the Pondok Pesantren Darussalam Blokagung Karangdoro Tegalsari Banyuwangi. Data obtained from observations, interviews, and documentation. The results of the study indicate that the implementation of adab guidance aims to help students recognize the etiquette that students should have. The method used in the guidance of the manners of the male students of the Darussalam Islamic Boarding School Blokagung is by using the method of dhikr, lectures and discussions or questions and answers. The method of studying the book of Adab Al 'Alim wal Muta'allim male students of the Darussalam Islamic Boarding School is to use the Sorogan, Bandongan (Wetonan) and Musyawarah (Halaqoh) methods. The adab material in the book of Adab Al 'Alim wal Muta'allim for students at Pondok Pesantren Darussalam Blokagung focuses on the material of Santri's etiquette towards himself, Santri's etiquette towards Ustadz, Santri etiquette towards lessons, and Santri's adab books (textbooks) as a tool for learning. The application of santri etiquette contained in the Adab Al 'Alim wal Muta'allim book at the Darussalam Islamic Boarding School Blokagung is quite good, although there are still some adab that have not been applied thoroughly. The results of this study are expected to be information and input for students, researchers and all parties in need in the Islamic Da'wah and Communication Faculty IAIDA Blokagung Tegalsari Banyuwangi.